Res. ANGRAU 52 (2) 111-121, 2024 *Corresponding Author E-mail i.d: khshitle.phd@gmail.com, Part of Ph.D thesis submitted to Manipur University, Canchipur - 795003 IMPACT OF TURMOIL ON PINEAPPLE PRODUCTION IN MANIPUR: A SCENARIO-BASED FORECAST - KHURAIJAM SHITLE KUMAR; SALAM SHANTIKUMAR SINGH (The Journal of Research ANGRAU, 2024)
The current turmoil in Manipur State has significantly impacted agriculture, likely to reduce agricultural or horticultural productions including pineapple. Traditional forecasting models typically assume ideal conditions and may not account for such extreme events. This study forecasts pineapple production using Regression, ARIMA, and ARIMAX models, incorporating cultivation area series to train the data. The high correlation (0.8979) between production and cultivation area supports using the area series as a covariate. For scenario-based forecasting, the cultivation area series is generated/simulated anticipating the impact of the turmoil on the cultivation area. The regression model explains 90.68% of the variance in production series, the ARIMA model (0, 2, 2) explains 81.79%, and the ARIMAX model explains 89.17%, effectively capturing changes in cultivation area. This study suggests that the Regression and ARIMAX models can provide realistic forecasts by considering anticipated changes in cultivation areas using scenario-based simulation of cultivation area making them adaptive to change in cultivation area.